International Capital Markets : Developments and Prospects, 1984 - Watson, Maxwell; Keller, Peter; Mathieson, Donald (Washington, D.C. : International Monetary Fund, 1984)
This paper provides a description and analysis of recent developments in international capital markets and an assessment of the prospects for private financing flows, in particular to the developing countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet